Climate Change, Humans, and the Extinction of the Woolly Mammoth - Nogués-Bravo, David; Rodríguez, Jesús; Hortal, Joaquín; Batra, Persaram; Araújo, Miguel B (PLOS Biology, 2008)
Climate models together with population models provide quantitative evidence that the combined effects of climate change and anthropogenic pressures can explain the extinction of the woolly mammoths.